Influenza virus infection increases ACE2 expression and shedding in human small airway epithelial cells. Issue 1 (1st July 2021) - Schweitzer, Kelly S.; Crue, Taylor; Nall, Jordan M.; Foster, Daniel; Sajuthi, Satria; Correll, Kelly A.; Nakamura, Mari; Everman, Jamie L.; Downey, Gregory P.; Seibold, Max A.; Bridges, James P.; Serban, Karina A.; et al.
Background: Patients with coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) demonstrate high rates of co-infection with respiratory viruses, including influenza A (IAV), suggesting pathogenic interactions. Methods: We investigated how IAV may increase the risk of COVID-19 lung disease, focusing on the receptor angiotensin-converting enzyme (ACE)2 and the protease TMPRSS2, which cooperate in the intracellular uptake of SARS-CoV-2. Results: We found, using single-cell RNA sequencing of distal human nondiseased lung homogenates, that at baseline, ACE2 is minimally expressed in basal, goblet, ciliated and secretory epithelial cells populating small airways. We focused on human small airway epithelial cells (SAECs), central to the pathogenesis of lung injury following viral infections. Primary SAECs from nondiseased donor lungs apically infected (at the air–liquid interface) with IAV (up to 3×10 5  pfu; ∼1 multiplicity of infection) markedly (eight-fold) boosted the expression of ACE2, paralleling that of STAT1, a transcription factor activated by viruses. IAV increased the apparent electrophoretic mobility of intracellular ACE2 and generated an ACE2 fragment (90 kDa) in apical secretions, suggesting cleavage of this receptor. In addition, IAV increased the expression of two proteases known to cleave ACE2, sheddase ADAM17 (TACE) and TMPRSS2 and increased the TMPRSS2 zymogen and its mature fragments, implicating proteolytic autoactivation. Conclusion: These results indicate that IAV amplifies the expression of molecules necessary for SARS-CoV-2 infection of the distal lung. Furthermore, post-translational changes in ACE2 by IAV may increase vulnerability to lung injury such as acute respiratory distress syndrome during viral co-infections. These findings support efforts in the prevention and treatment of influenza infections during the COVID-19 pandemic. Influenza virus infection of cells lining the small airways increases the expression of molecules required for SARS-CoV-2 uptake in a manner that predicts increased severity of lung disease in those co-infected with influenza and coronaviruses https://bit.ly/3nu1WAo